2(x - 1)(2x + y)
2xy - 4x plus 8y - 16 equals x plus 4 in parentheses multiplied by 2y minus 4 in parentheses. So, the factors are ( x + 4) and ( 2y - 4) .
ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X
4x^2+2xy-3y^2-2x^2+5xy-2y2Collect the like terms=2x^2+7xy-5y^2We cannot factorise it because the end term is a negative whilst the second-last term is positive.
4x+2y = 20 2y = -4x+20 y = -2x+10
4x2 - 4x + 2xy - 2y = 4x(x - 1) + 2y(x - 1) (4x + 2y)(x - 1).
2(x - 1)(2x + y)
2xy - 4x plus 8y - 16 equals x plus 4 in parentheses multiplied by 2y minus 4 in parentheses. So, the factors are ( x + 4) and ( 2y - 4) .
2 (2x2 + 2x + xy + y ) it's 2 (2x + y)(x + 1) if you're doing A+
4x-2y+3x+2y When simplified: 7x
(2xy-4x)+ (8y-16)=2xy-4x+8y-16, which factors as 2(x+4)(y-2)
When factoring an expression we are attempting to find two or more numbers or expressions that when multiplied will result in our starting expression. For example, to factor 12 we would say 2*2*3 because when multiplied, it would equal 12. To factor this expression, start by grouping both sides with parentheses. 4x^2-4x+2xy-2y (4x^2-4x) + (2xy-2y) Now use reverse distribution to pull a 4x out of the first part and a 2y out of the second. (4x^2-4x) + (2xy-2y) 4x(x-1) + 2y(x-1) looking at the expression as a whole we see that both terms have a factor of x-1. So, we reverse distribute again to get a factored expression 4x(x-1) + 2y(x-1) (x-1)(4x+2y) Factor out a two from the second expression to get the final, fully factored answer. (x-1)(4x+2y) 2(x-1)(2x+y)
ANSWER: -4X2 -8X-4x (x+2)= (-4x * x) + (-4x*2)= -4X2 -8X
( 2xy - 4x ) + ( 8y - 16)2 ( xy - 2x ) + 2 ( 4y - 8 ) Answer
4x^2+2xy-3y^2-2x^2+5xy-2y2Collect the like terms=2x^2+7xy-5y^2We cannot factorise it because the end term is a negative whilst the second-last term is positive.
4x+2y=24 => 2y=24-4x => y=12-2x and the slope is -2
4x+2y = 20 2y = -4x+20 y = -2x+10